PENGEMBANGAN APLIKASI MANAJEMEN PELANGGAN WIFI BERBASIS WEB DI HH.NET (MAJA BANTEN) - lestari, ela (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
In this modern era, technology continues to grow and one of them is the internet. The internet in this day and age is needed in order to facilitate human work. In its development, current internet use can be connected to homes through internet service provider companies where each customer can register their internet needs with various choices of speed levels based on internet speed units or commonly called Megabits Per Second (Mbps). HH. Net is an internet service provider company that focuses on selling, installing and maintaining internet connections. Internet customer registration process at HH. Net so far still uses a manual system, where prospective customers fill out a registration form which is then processed to enter data by the administrative section into the Microsoft Excel application which then produces a recap of internet installation registration. The recording of wifi customer data on HH.Net is still on a conventional basis, causing data loss. The purpose of making this Web-Based Internet Registration Information System is that internally it can facilitate management in making decisions and from the external side it can make it easier for internet customers to obtain information.